The place of communication in democratic theories - Feres Júnior, João (2024)
The text begins by identifying the central role of communication in the functioning of democracy. Firstly, we examine this role in the context of Athenian direct democracy from the classical period. Next, we identify the transformations brought about by the reinvention of democracy, now in its representative variant, starting from the Age of Revolutions. Following that, we undertake an analytical exercise to identify the functions and requirements related to communication according to the three main currents of democratic theory: representative (aggregative), deliberative, and participative.